Systematic review on the prevalence of illness and stress and their associated risk factors among educators in Malaysia - Tai, Kwee Ling; Ng, Yee Guan; Lim, Poh Ying (Public Library of Science, 2019)
Background Despite evidence of physical (illness) and mental (stress) health problems, there appears to be a lack of studies or concern regarding occupational safety and health among educators in Malaysia. Objective To review the prevalence of illness, stress, and corresponding risk factors among educators in Malaysia. Method Scopus, ProQuest, PubMed, ScienceDirect, CAB, and other computerized databases were searched according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to identify studies published between January 2013 and April 2019 on the prevalence and associated risk factors of illness and stress among educators (S1 Checklist). The keywords used included educator, teacher, lecturer, academic staff, teaching profession, university staff, academician, faculty, illness, injury, disease, pain, WMSD, dysphonia, hoarseness, stress, mental health, strain, health problem, disorder, and/or Malaysia. Selected studies were evaluated by quality assessment. Results Twenty-two articles fulfilled the eligibility criteria. The prevalence of illness and stress was determined for low back pain (33.3–72.9%); upper back pain (33.33–56.4%); neck/shoulder pain (40.4–80.1%); upper arm discomfort (91.3%); forearm pain (89.6%); wrist pain (16.7–93.2%); hip pain (13.2–40.9%); thigh discomfort (91.8%); lower leg discomfort (90.5%); knee pain (23.7–88.0%); ankle/feet pain (19.3–87.7%); elbow pain (3.5–13.0%); voice disorder (10.4–13.0%) and stress (5.5–25.9%). Sex, education level, teaching experience, quality of life, anxiety, depression, coping styles, and others were reported as associated risk factors across the studies. Conclusions There appears to be a cause for concern regarding musculoskeletal disorders, voice disorder, and stress reported among educators in Malaysia. While most risk factors matched those reported in studies elsewhere, others such as school characteristics (school level, government or private school, and location [rural/urban]) have not been investigated.